Quantifying Recent Upsurge in Covid-19 Incidence and Related Fatalities: An Implication of Delayed Response or State of Delivery Health Care System? - Taofik Olatunji Bankole; Glory Urhere (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
Study Aim: To validate the recent upsurge in COVID-19 incidence and related fatalities in a retrospective to the state of the healthcare delivery system and delayed in response to the pandemic in Nigeria. Methods: The quantitative cross-sectional times series method was adopted. COVID-19 Data for Nigeria were extracted for reported cases and fatalities arising from COVID-19 complications from the WHO COVID-19 situational data bank between March 15 and July 15, 2020. The incidence and fatality growth rates were generated at intervals for four months. Data were analyzed with the Stata version 15. Results: Findings showed that the recent upsurge in COVID-19 accounted for 99.2%, 98.9%, 98.5%, 99.8%, 99.2%, 99.8%, and 97.3% complications that led to the death of infected patients in the Northcentral, Northeast, Northwest, Southeast, Southsouth. Southwest and the FCT. The results showed that there was a strong uphill linear (r = 0.991) and a significant association between COVID-19 incidence and fatalities arising from COVID-19 complications in Nigeria (ß = 0.022; t = 30.2; p<0.001).